Psychosis and identity: Alteration or loss?. Issue 5 (1st June 2017) - Gergel, Tania; Iacoponi, Eduardo
Abstract: The onset of psychotic disorders often brings major changes to an individual, which, for some, are never fully reversed and remain a dominant force. Despite such changes, the individual still experiences themselves as a continuous person and must find some way to assimilate these shifts into their self‐concept. From a philosophical perspective, the various models of continuing identity all depend upon some notion of fundamental stability, which seems a poor fit for the trajectory associated with psychotic disorders. This article will explore, in more depth, how the transitions that accompany psychotic disorders present a challenge to conventional and philosophical notions of selfhood. If we are not simply to judge psychotic disorders as bringing about a loss of selfhood, we will need an alternative model of identity to use in this context.